Phyton-Based Machine Learning Algorithm To Predict Obesity Risk Factors In Adult Populations - Mari Rahmawati; Ade Fitria Lestari; Sri Hardani (LPPM Universitas Bina Sarana Informatika, 2024)
Obesity is a serious health problem because it can lead to a variety of diseases. Adults are prone to obesity due to several factors such as age, physical activity, weight, diet, gender, lifestyle and so on. Machine Learning as one of the methods for predicting and classifying factors of obesity especially in the adult population. In machine learning, there are various types of algorithms that can be used to classify data. In this study, using the K-Nearest Neighbor, Decision Tree and Naïve Bayes algorithms, 2111 datasets were used and processed using the Phyton programming language. The results were obtained from the comparison of the three algoritms with the highest accuracy of 93.6%, the Decision Trees with 79.6% and the Naïv Bayes with 60%.